Case Series of Intrauterine Subamniotic Hemorrhage - Momoko Owada; Yoshie Shibata; Shunji Suzuki (Case Reports in Obstetrics and Gynecology)
We present here 9 cases of intrauterine subamniotic hemorrhage to describe the pathological sequence. The definite diagnosis of subamniotic hemorrhage was mainly made macroscopically with the presence of hemorrhage or hematoma wrapped in the membrane on the fetal surface by postnatal examining of the placenta. In 7 of them (78%), the presence of gradual subamniotic hemorrhage in the second trimester of pregnancy was suspected. In the cases, severe fetal growth restriction and preterm delivery were recognized in 2 (29%) and 4 cases (57%), respectively. In the other 2 cases (22%), acute anemia associated with acute subamniotic hemorrhage was clinically suspected. This may be the first report examining the clinical characteristics of acute or gradual intrauterine subamniotic hemorrhage. Both patterns of subamniotic hemorrhage seemed to be associated with the adverse perinatal outcomes.